Arkansas, Arkansas Volume 1 : Writers and Writings from the Delta to the Ozarks, 1541-1969 - Guilds, John Caldwell, 1924- (Book collections on Project MUSE., 1999)
"An anthology of work by natives of the southern state and others who have written about it. The travel writing, biography, history, poetry, and fiction are selected to reflect both the state's unity and its sometimes extreme cultural, political, and topographical differences. The first volume spans the period from the 16th century to 1970. There is no index or bibliography." -- Publisher.